Production of Eudrilus eugenia and Compost From Breeding Manure (Cattle, Cavies, Rabbits, And Poultry) In South Of Côte D’ivoire - Kouakou Parfait KOUADIO; Soronikpoho SORO; Grace Garacha; Gattien Brou; Yadé René SORO; Kouhana SORO (Warmadewa University Press, 2023)
Developing countries must, in order to support agriculture, integrate available natural resources and promote management of livestock waste. Therefore, the potential of earthworms to decompose organic waste must be exploit : vermicomposting. Thus earthworm Eudrilus eugeniae was cultured in 4 simples treatments and 6 mixed manure treatments. These treatments are combination or not of manure of cattle, cavies, rabbit and poultry. Each treatment has undergone 3 repetitions. The experiment lasted 12 weeks. pH, numerical productivity of E. eugeniae and biomass of E. eugenia have been determined. The results showed that all treatments containing rabbit manure have a final pH close to 7 (neutral pH) with the exception of MG +MR treatment. Those based on poultry or guinea-pig manure and the control range between 5 and 6.5 and are therefore more acidic. The average density and the earthworm biomass of the MC + MR treatment respectively 2889 ± 333 ind./ m2 and 397.22 ± 234.44 g / m2 are different from other treatments. the manure mixture is a privileged environment for Eudrilus eugeniae. It provides a significant biomass of earthworms that can be used in fish farming or in the diet of monogastric animal feed.